Antibacterial activities of hexadecanoic acid methyl ester and green‐synthesized silver nanoparticles against multidrug‐resistant bacteria. (19th April 2021) - Shaaban, Mohamed T.; Ghaly, Mohamed F.; Fahmi, Sara M.
Abstract: Antibacterial drug resistance is considered one of the biggest threats to human health worldwide, and the overuse of antibiotics accelerates this problem. Multidrug‐resistant (MDR) bacteria are becoming harder to treat as the antibiotics used to treat them become less effective. Therefore, it is necessary to evaluate novel methods to control MDR bacteria. In this study, 40 bacterial isolates were collected from diabetic patients. The sensitivity of 40 bacterial isolates to seven antibiotics was evaluated. Four bacterial isolates were resistant to all antibiotic groups. The MDR pathogenic bacteria were selected and identified morphologically and biochemically and confirmed by VITEK® 2 system as follows: Staphylococcus aureus W35, Pseudomonas aeruginosa D31, Klebsiella pneumoniae DF30, and K. pneumoniae B40. Identification of the most resistant P. aeruginosa D31 was confirmed by the sequencing of a 16S ribosomal RNA gene with an accession number (MW241596). The inhibitory activity of eight types of native grown plant extracts against MDR bacteria was studied. Clove alcoholic extract (CAE) showed the highest inhibitory activity against MDR bacteria. Gas chromatography–mass spectrometry analysis of partially purified CAE at 0.9 Rf detected by thin‐layer chromatography showed an active compound named hexadecenoic acid methyl ester with the highest antimicrobial effect against clinical pathogenic bacteria. The formation of silver nanoparticles (AgNPs) by CAE was studied. Evaluation of AgNPs was investigated by X‐ray diffraction, UV–Vis, and transmission electron microscopy. The antibacterial effect of AgNPs after 2, 4, and 6 days in light and dark conditions was evaluated. Finally, the AgNPs synthesized using CAE possess good inhibition activity against the tested pathogenic bacteria. As a result, the bactericidal components listed above were promising in reducing MDR bacteria and can be used for treatments of bacterial infection and in the development of safe products with a natural base.